2020
DOI: 10.1371/journal.pone.0237510
|View full text |Cite|
|
Sign up to set email alerts
|

Self-reported and clinical periodontal conditions in a group of Eastern European postpartum women

Abstract: Periodontitis is a highly prevalent condition leading to a continuous destruction of tooth-supporting tissues. It increases the risk for various systemic diseases and adverse pregnancy outcomes. Therefore, screening for periodontitis is important. Screening measures can range from self-reported symptoms to clinical full-mouth periodontal examination. The hypothesis of our study was that self-reported parameters and clinical definition perform equally well in identifying periodontitis patients. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Of interest is the association of ‘mouth rinse use’ with SP (OR = 5.60). This concurred with findings from a US study which showed association of mouth rinse use with SP [ 43 ], though there were many other studies which did not show any evidence of such association [ 17 , 18 , 22 , 25 , 26 ]. This highlights the importance of validating any self-report measures in a given population due to differences in population-specific characteristics, access to dental care, cross-cultural adaptation of questionnaire items and periodontitis prevalence [ 10 , 13 , 15 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of interest is the association of ‘mouth rinse use’ with SP (OR = 5.60). This concurred with findings from a US study which showed association of mouth rinse use with SP [ 43 ], though there were many other studies which did not show any evidence of such association [ 17 , 18 , 22 , 25 , 26 ]. This highlights the importance of validating any self-report measures in a given population due to differences in population-specific characteristics, access to dental care, cross-cultural adaptation of questionnaire items and periodontitis prevalence [ 10 , 13 , 15 , 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…Higher validity can thus be achieved with a combination of self-reported questions, demographic and risk factor variables [ 10 ]. Since then, the validity of self-reporting for periodontitis has been tested in different Western populations [ 14 , 15 , 20 , 21 , 22 , 23 ], including high-risk populations in rural areas [ 24 ], African Americans [ 25 ] and post-partum women [ 26 ]. Very few studies have been carried out in Asian populations, mainly in China [ 27 ] and Japan [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis case definitions were applied by four experienced, highly trained periodontologists (A.R., S , .I.S., I.C.M., P.D.M.) [45,52,53].…”
Section: Aap/cdc Periodontitis Case Definitionmentioning
confidence: 99%
“…Experienced investigators previously calibrated (A.C., A.S., I.C.M) [ 49 , 50 ], and one young specialist (C.S.C.) dealt with the periodontal examinations.…”
Section: Methodsmentioning
confidence: 99%